THE PREDICTING FACTORS FOR CHRONIC KIDNEY DISEASE AMONG HIGH-RISK POPULATION IN LOWER NORTHERN, THAILAND - Konkaew, Primprapha; Pattama Suphunnakul (Malaysian Journal of Public Health Medicine, 2020)
This research aimed to explore the factors predicting chronic kidney disease (CKD) in the high-risk population. A cross-sectional study had been conducted in the high-risk populations investigated with and without CKD were the participants. A total of 1,463 samples was enrolled by a multistage sampling technique was used to recruit participants from five provinces in the lower northern of Thailand. Data were collected using a questionnaire and analyzed with descriptive statistics, and binary logistic regression. The results were revealed the risk factors affecting CKD including aged, dyslipidemia, being ill of diabetes mellitus, being unable to control blood pressure, being unable to control blood sugar level, taking add more salty seasoning to the cooked food, cooking with sodium salt over the prescribed amount, using the non-steroidal anti-inflammatory drug, lack of exercise, herbal plants consumption as drugs that are toxic to the kidney, edema, foamy urine, and nocturia. All risk factors were able to co-predict the risk to CKD about 83.2% at the 0.05 level of significance. Therefore, to prevent early states with CKD in the high-risk populations, the focus should be on encouraging health literacy because health literary it has a positive relationship with health-promoting behaviors. The health care provider needs to concentrate on increasing health literacy for self– management with them.